2010
DOI: 10.1007/s11249-010-9646-9
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and Fundamental Properties of Novel Lubricant TA-30 for Near Contact Magnetic Recording

Abstract: A novel perfluoropolyether (PFPE) lubricant called TA-30 has been developed recently. We investigate the conformation of TA-30 on diamond-like carbon (DLC) thin films, by attempting the direct observation of a lubricant film by atomic force microscopy (AFM) using a fluoride probe. We investigate the fundamental properties of a TA-30 lubricant film, such as its spreading characteristics, and the film thickness dependence of surface energy. Considering these experimental results, we conclude that the conformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…These aspects are well-understood in terms of the barriers to internal rotation and chain confinement effects due to the pendant branch and are therefore fully anticipated results [3,4]. We also note that the monolayer thickness derived from the terraced flow for TA-30 reported here, ~ 18 Å, is substantially larger than reported by Tagawa et al, ~ 9 Å [11]. A reason for this difference is not yet understood.…”
Section: Resultssupporting
confidence: 52%
“…These aspects are well-understood in terms of the barriers to internal rotation and chain confinement effects due to the pendant branch and are therefore fully anticipated results [3,4]. We also note that the monolayer thickness derived from the terraced flow for TA-30 reported here, ~ 18 Å, is substantially larger than reported by Tagawa et al, ~ 9 Å [11]. A reason for this difference is not yet understood.…”
Section: Resultssupporting
confidence: 52%
“…Tagawa et al have recently shown that TA-30 shows more slider-disk clearance than Z-Tetraol at similar film thicknesses [23]. We have also conducted sliderdisk clearance measurements on Z-Tetraol, D-4OH, and TA-30 at the same 11 Å film thickness on identical carbon films (amorphous nitrogenated carbon films).…”
Section: Discussionmentioning
confidence: 86%
“…For example, removing the -(CF 2 O)-monomer unit in -(CF 2 O) p -(CF 2 CF 2 O) q -is one way in which chain flexibility can be reduced. Consequently, PFPEs derived from -(CF 2 CF 2 O)-, or -(CF 2 CF 2 CF 2 O)-, or -(CF 2 CF 2 CF 2 CF 2 O)monomer units are increasingly being utilized [9,10].…”
Section: Introductionmentioning
confidence: 99%